Neurospora Bibliography - Craig Wilson (Fungal Genetics Reports, 2001)
This bibliography represents my attempt to collect all works dealing substantially with Neurospora. Please let me know of anything published in 2000 or 2001 that is not included here or in the previous bibliography, so that it might be mentioned next year.